Blood transfusion from a Hb e trait donor can affect β-thalassemia diagnosis - Sakorn Pornprasert (2018)
A subject with Hb E (HBB: c.79G > A) trait is asymptomatic and can become a blood donor. However, a blood transfusion from a Hb E trait donor can affect β-thalassemia (β-thal) diagnosis. Blood samples from three Thai women were sent to the Associated Medical Sciences (AMS) Clinical Service Center, Chiang Mai, Thailand, for thalassemia diagnosis. Their Hb A2 levels, analyzed by high performance liquid chromatography (HPLC), were higher than 4.0%, thus they were diagnosed to have β-thal. However, elevated Hb A2 levels in these patients were not certain because the Hb A2 levels analyzed at the initial hospitalization and follow-up were controversial. In addition, there were some cases shown to have controversy between the increased Hb A2 level and red cell indices. The blood transfusion history was confirmed and hemoglobin (Hb) analysis was reanalyzed by capillary electrophoresis (CE). On the CE electrophoregram, Hb A2 levels were observed to be normal and Hb E peaks were present. Therefore, to rule out misdiagnosis and unnecessary genetic counseling, Hb analysis should be performed on the recipient prior to blood transfusions. Moreover, CE has a high efficiency to prevent the misinterpretation of Hb analysis in patients who receive blood transfusions from a donor carrying Hb E. © 2014 Informa Healthcare USA, Inc. All rights reserved: reproduction in whole or part not permitted.